Gambling with antibiotics: a novel approach for exploring antibiotic consumption decision-making. (October 2017) - Naylor, N.R.; Uchegbu, I.; Chatterjee, A.; Robotham, J.V.
Highlights: Standard gamble approach is used to explore the propensity for wanting antibiotics. The public seem more reluctant to want antibiotics when effectiveness is reduced. Mention of negative community impact did appear to alter public decision-making. Future work should utilise representative samples and hypothesis testing techniques.